PENERAPAN PROGRESSIVE MUSCLE RELAXATION DAN GUIDED IMAGERY DALAM MENGATASI KELUHAN KECEMASAN PASIEN KANKER YANG MENJALANI KEMOTERAPI - Nur Febrianti (Stikes Graha Edukasi Makassar, 2018)
Objective: This literature study aims to analyze research on progressive muscle relaxation and guide imagination as a complementary therapy in dealing with patient complaints after chemotherapy. Method: Journal search related topics raised in December 2017 by entering terms or phrases on databases and resources available on the internet. The first major search strategy focuses on PubMed and Google Scholar databases. Results: The final result of the journal or article selection was obtained and conducted 14 journals consisting of systematic reviews, RCTs, and quasi-experimental studies. Discussion: Cancer is still a health problem and is the second leading cause of death in the world. Chemotherapy is the most common cancer treatment in these cancer patients, although it has side effects. Therefore, it is necessary complementary therapies to reduce the side effects of chemotherapy. Conclusions: This literature study shows that PMR and GI may decrease anxiety in cancer patients undergoing chemotherapy